Immediate Effects of Kinesio Taping on pain in Athletes with Patellofemoral Pain Syndrome - Rehman, Neelam; Kashif, Muhammad; Sajjad, AbdulGhafoor; Hassan, Hafiz Muhammad Junaid; Iram, Humaira (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2020)
Background Ligaments injury and anterior knee pain is the most common problem in the knee joint. In practice, there are various interventions for the treatment of patellofemoral pain syndrome (PFPS). Kinesio taping is one of them, but little literature is available on the immediate effects of treating this problem.Methodology From June to September 2017, a randomized control study was conducted at the Army Sports Complex GHQ Rawalpindi to determine the effectiveness of Kinesio Taping (KT) in patellofemoral pain syndrome in athletes. Data were collected from 48 athletes who fully met the inclusion criteria and were randomly divided into 2 groups. The data collection tool was Numerical Pain Rating Scale (NPRS), Kujala PFPS Score, and self-structured Questionnaire. The data was analyzed on SPSS 21.Results The overall mean age was 22.7±3.0. The immediate effects showed improved NPRS in both groups; in the control group the NPRS pre 1st visit mean was 5.36±1.2 and post 1st visit mean was 4.68±1.3 with the difference of 0.68±0.1 having p value p<0.001. In the treatment group the NPRS pre 1st visit mean was 5.90±1.2 and post 1st visit mean was 5.00±1.0 with the difference of 0.90±0.1 having p value p<0.001.Conclusion This study shows immediate effects of Kinesio-Taping, however there was not any significant difference between both groups but the treatment group performed well after the sessions.Hintergrund Bänderverletzungen und vorderer Knieschmerz sind die häufigsten Beschwerden des Kniegelenks. In der Praxis existieren viele unterschiedliche Behandlungsmethoden für das patellofemorale Schmerzsyndrom (PFSS). Kinesio-Taping ist eine davon – es ist jedoch wenig Literatur über die unmittelbare Wirkung dieser Methode verfügbar. Methoden Im Army Sports Complex GHQ in Rawalpindi, Indien, wurde von Juni bis September 2017 eine randomisierte kontrollierte Studie durchgeführt, um die Wirksamkeit von Kinesio-Taping auf das patellofemorale Schmerzsyndrom bei Sportlern zu bewerten. An der Studie nahmen 48 Sportler teil, die alle die Einschlusskriterien erfüllten und zufällig in 2 Gruppen aufgeteilt wurden. Die Daten wurden mittels Numerischer Rating-Skala (NRS) für Schmerzen, dem funktionellen Patella Score (Kujala Score) und einem selbst auszufüllenden Fragebogen erhoben. Die Daten wurden mit SPSS 21 analysiert.Ergebnisse Das Durchschnittsalter aller Teilnehmer betrug 22,7±3,0. Als unmittelbare Wirkung zeigten beide Gruppen eine verringerte Schmerzintensität auf der Rating-Skala (NRS); in der Kontrollgruppe wurde auf der NRS vor der 1. Visite 5,36±1,2 und nach der 1. Visite 4,68±1,3 angegeben; die Differenz betrug 0,68±0,1 mit einem p-Wert von p <  0,001. In der Taping-Gruppe wurde auf der NRS vor der ersten Visite 5,90±1,2 und nach der ersten Visite 5,00±1,0 angegeben; die Differenz betrug 0,90±0,1 mit einem P-Wert von <0,001.Schlussfolgerung Diese Studie belegt die unmittelbare Wirkung von Kinesio-Taping, es gab jedoch keinen signifikanten Unterschied zwischen den beiden Gruppen – aber die klinische Erprobungsgruppe zeigte nach den Behandlungen gute Ergebnisse.
Keywords: Athletes; Kinesio Taping; Patellofemoral Pain Syndrome; Sports Physiotherapy